2014
DOI: 10.5562/cca2272
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds in Centaurea rupestris Tissues and Their Antiphytoviral Activity

Abstract: Abstract. Quantitative and qualitative analysis of phenolic compounds in tissue extracts from Centaurea rupestris L. as well as their antiphytoviral activity against Tomato bushy stunt virus was performed. Extracts of flowers, leaves and roots from C. rupestris growing in the wild, as well as extracts from shoots, tissue consisting of callus and shoots and undifferentiated callus grown in vitro, were tested. Between tested extracts predominantly quantitative and only several qualitative differences in phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The anticancer activity of extracts from Centaurea species has been furthermore confirmed by a study conducted on the Turkish endemic plant C. drabifolia which revealed antiproliferative activity against leukemia cells (Formisano et al2017). Previous studies also reported anti-inflammatory activities of C. sadleriana (Csupor et al 2013) and more recently antiphytoviral activity against Tomato bushy stunt virus for phenolic compounds isolated from C. rupestris (Curkovic-Perica et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…The anticancer activity of extracts from Centaurea species has been furthermore confirmed by a study conducted on the Turkish endemic plant C. drabifolia which revealed antiproliferative activity against leukemia cells (Formisano et al2017). Previous studies also reported anti-inflammatory activities of C. sadleriana (Csupor et al 2013) and more recently antiphytoviral activity against Tomato bushy stunt virus for phenolic compounds isolated from C. rupestris (Curkovic-Perica et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…[15 -19] Centaurea salonitana is known for its anti-inflammatory and wound healing properties, [20] while the phenolic compounds of C. rupestris have shown good antiphytoviral activity, along with the antimicrobial activity of the essential oil tested previously. [21,22] Plant secondary metabolites mixtures, such as volatile oils (VOs), may contain chemical compounds that are characteristic of certain species and whose study is of interest for phytotaxonomy. The common constituents of the Centaurea species' volatile oils belong to a group of non-oxygenated and oxygenated terpenes, together with the non-oxygenated hydrocarbon derivatives, while oxygenated hydrocarbon derivatives make up a smaller part of VOs.…”
Section: Introductionmentioning
confidence: 99%
“…Many Centaurea species are known to be valuable sources of pharmacologically active compounds and have been used in traditional medicine to treat various diseases and ailments [15–19] . Centaurea salonitana is known for its anti‐inflammatory and wound healing properties, [20] while the phenolic compounds of C. rupestris have shown good antiphytoviral activity, along with the antimicrobial activity of the essential oil tested previously [21,22] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation